Effects of follicle-stimulating hormone on fat metabolism and cognitive impairment in women during menopause - Mao, Liwei; Wang, Lian; Bennett, Samuel; Xu, Jiake; Zou, Jun (Frontiers in Physiology, 2022)
Lipid metabolism disorder is a common pathological manifestation of menopausal women and is also an important risk factor for many diseases at this stage of life. Epidemiological studies have shown that high levels of follicle-stimulating hormone (FSH) in menopausal women are closely associated with changes in body composition, central obesity, and cognitive decline. Exogenous FSH causes growth and proliferation of adipose, whereas blockage of the FSH signaling pathway leads to decline in adipose. Mechanistically, FSH, FSH receptor (FSHR), G protein coupling, gene mutation and other pathways are involved in adipogenesis and cognitive impairment. Here, we review the critical role and potential interactions of FSH in adipogenesis and cognitive impairment in menopausal women. Further understanding of the exact mechanisms of FSH aggravating obesity and cognitive impairment may provide a new perspective for promoting healthy aging in menopausal women.